2018
DOI: 10.1016/s2214-109x(18)30385-1
|View full text |Cite
|
Sign up to set email alerts
|

Population-based rates, timing, and causes of maternal deaths, stillbirths, and neonatal deaths in south Asia and sub-Saharan Africa: a multi-country prospective cohort study

Abstract: SummaryBackgroundModelled mortality estimates have been useful for health programmes in low-income and middle-income countries. However, these estimates are often based on sparse and low-quality data. We aimed to generate high quality data about the burden, timing, and causes of maternal deaths, stillbirths, and neonatal deaths in south Asia and sub-Saharan Africa.MethodsIn this prospective cohort study done in 11 community-based research sites in south Asia and sub-Saharan Africa, between July, 2012, and Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
183
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(207 citation statements)
references
References 19 publications
10
183
3
Order By: Relevance
“…Maternal and neonatal mortality remain a global health concern despite different interventions that have been implemented to address this issue [1]. Sub-Saharan Africa (SSA) is by far among the regions with the highest ratios of maternal mortality with 351 per 100 000 live births and high neonatal mortality rates with 20 per 1000 live births [2]. Several studies have shown that 15% of maternal and newborn deaths in SSA are attributed to pregnancy complications that are a result of inadequate pregnancy follow-up [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and neonatal mortality remain a global health concern despite different interventions that have been implemented to address this issue [1]. Sub-Saharan Africa (SSA) is by far among the regions with the highest ratios of maternal mortality with 351 per 100 000 live births and high neonatal mortality rates with 20 per 1000 live births [2]. Several studies have shown that 15% of maternal and newborn deaths in SSA are attributed to pregnancy complications that are a result of inadequate pregnancy follow-up [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Poor quality of care contributes to morbidity and mortality, and therefore attention has shifted to the quality of care. In low-and middle-income countries (LMIC), the challenge has been the need for balancing coverage with quality.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Poor quality of care contributes to morbidity and mortality, and therefore attention has shifted to the quality of care. 2 A significant contributor to the neonatal mortality rate was birth asphyxia, with only prematurity occurring more frequently. 6 The disease burden is high, particularly in LMIC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations